Physical activity programs in patients with Alzheimer’s disease: what does the practice based on evidence in physiotherapy? - Pedro, Luisa (2017)
Objectives: Alzheimer’s disease is progressive and irreversible and results in cognitive and/or motor disturbances. The objectives of this study are to review the literature-based evidence on the efficacy of a physical activity program designed by physical therapy in controlling the progression of Alzheimer’s disease. Method: The research was performed in the databases MEDLINE and PEDRO, where articles in English and Portuguese idioms published from 2011 to 2016 were selected. We used the following keywords: “Alzheimer's” and “physical activity” and “physiotherapy”, having as result 112 articles in MEDLINE, and 21 in PEDRO. We applied the following Exclusion criteria in the selection of articles: All articles that did not register data recommendation for physiotherapy, those patients submitted to pharmacological tests. At the end articles, 18 were selected. Results: The studies recommend performing the aerobic exercise of moderate intensity for a total of 20 to 30 minutes per session, alternating with rest periods, two to three times per week, have benefits for a cognitive component of these patients. The balance training improves the posture of individuals affected by Alzheimer’s disease, and thereby reduce the risk of falling. The program of activities including, aerobic exercise (walking, swimming, cycling) and strength training, proved to be particularly effective in improving posture and reducing the risk of fall as well as improved physical function and cognitive these patients. Conclusion: We found scientific evidence that exercise programs and physical activity promotion in people with Alzheimer’s disease. May have a significant impact on its functionality, and possibly to improve cognition in individuals with Alzheimer’s disease.